Match outcome and running performance in different intensity ranges among elite soccer players - Chmura, Paweł; Konefał, Marek; Chmura, Jan; Kowalczuk, Edward; Zając, Tomasz; Rokita, Andrzej; Andrzejewski, Marcin (Biology of Sport, 2018)
The monitoring of players’ work-rate profiles during competition is now feasible through computer-aided motion analysis. The aim of the present study was to examine how various playing positions and match outcomes (i.e. won, drawn, lost) affect the total distance, and the distances covered at different intensities, by soccer players in Germany’s Bundesliga. Match performance data were collected for 556 soccer players competing in the Bundesliga during the 2014/15, 2015/16 and 2016/17 domestic seasons. A total of 13 039 individual match observations were made of outfield players (goalkeepers excluded). The analysis was carried out using an IMPIRE AG motion analysis system, with records of all players’ movements in all the 918 matches. The recorded variables included total distance covered [km] and distance covered at intensities in the ranges below 11 km/h, 11-14 km/h, 14-17 km/h, 17-21 km/h, 21-24 km/h, and above 24 km/h. In won matches, as opposed to drawn and lost matches, the wide midfielders and forwards ran a significantly longer distance, primarily covered at intensities of 21-23.99 and above 24 km/h (p ≤ 0.05). The analysis of full-backs, central defenders and central midfielders in won matches – as opposed to drawn and lost matches – in turn reveals that players ran a significantly shorter distance, most likely to be covered at intensities of 17-20.99 and 21-23.99 km/h (p ≤ 0.05). The results of the present study emphasise the importance of match outcome and playing positions during the assessment of physical aspects of soccer performance.